Socrates questions to optimize students critical thinking - Rahmawati, Dwi; Vahlia, Ira; Mustika, Mustika; Yunarti, Tina; Nurhanurawati, Nurhanurawati (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
The ability to think critically is one of the abilities that must be possessed by students in facing the rapid development of the times. Students' critical thinking skills can be developed through Socratic questions. This research is to find out 1) the types of Socratic questions used in learning and 2) whether Socratic questions can optimize students' critical thinking skills. The method used is a qualitative and quantitative approach with a pretest-posttest one group design. The research subjects were mathematics education students who attended linear algebra courses at Muhammadiyah Metro University. Data collection was carried out through observation and tests with descriptive qualitative and quantitative data analysis techniques. Socratic questions asked by lecturers in learning linear algebra include questions of clarification, investigative assumptions, reasons, investigative evidence, and beliefs. Socrates' questions can stimulate students' critical thinking activities to strengthen their understanding of concepts. Students' critical thinking skills increased in the medium category. The types of Socratic questions used in learning are distinguished based on three stages, namely in the introduction stage, the types of questions asked by the lecturer are clarification questions. At the core stage, Socratic questions include questions of clarification, investigative assumptions, evidence/reasons, and beliefs. And in the concluding stage, Socrates' question is a clarifying question. Socratic questions used in learning can optimize students' critical thinking skills. The results of this study are expected to be a reference for lecturers in applying Socratic questions in learning, especially in linear algebra courses.